2022
DOI: 10.3390/su14116892
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Development Priority of Smart Shipping Items—Focusing on the Expert Survey

Abstract: As smart technology in the shipping industry accelerates, demand for technology development, which aims to increase competitiveness by utilizing the latest smart technologies, is increasing. The shipping industry in each country is pushing for developing its smart technologies at a rapid pace, and it is urgent to prioritize the demand for smart technologies in the shipping industry for sustainable industry growth. The purpose of the present study is to verify the importance and urgency of smart technologies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Our research further confirms a small positive indirect impact in the relationship: Contingencies -Digitalization -Functions -Benefits (O = 0.073, p = 0.000). This aligns with the more simplified research findings that indicate a positive correlation between digitalization of budgeting and corporate achievements: financial performance (Kindström & Kowalkowski, 2014), (Ghobakhloo, 2018), (Moeuf et al, 2018), (Sambrani & Jayadatta, 2020), but our findings relate to supporting and managerial processes, and support for company's sustainable development (Moreno-Monsalve et al, 2023), (Ahn et al, 2022), (Özkan et al, 2021), however, our findings relate to the overall budgeting system, not project budgeting.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our research further confirms a small positive indirect impact in the relationship: Contingencies -Digitalization -Functions -Benefits (O = 0.073, p = 0.000). This aligns with the more simplified research findings that indicate a positive correlation between digitalization of budgeting and corporate achievements: financial performance (Kindström & Kowalkowski, 2014), (Ghobakhloo, 2018), (Moeuf et al, 2018), (Sambrani & Jayadatta, 2020), but our findings relate to supporting and managerial processes, and support for company's sustainable development (Moreno-Monsalve et al, 2023), (Ahn et al, 2022), (Özkan et al, 2021), however, our findings relate to the overall budgeting system, not project budgeting.…”
Section: Discussionsupporting
confidence: 90%
“…Moreno-Monsalve et al conducted a study which showed that sustainable developmentoriented projects tend to create value, with four key dimensions -impact, relevance, effectiveness, and efficiencyplaying a significant role in explaining their success (Moreno-Monsalve et al, 2023). The strategic priorities related to sustainability are of high importance and urgency, and research showed that the prudent allocation of investment can enhance the sustainability and long-term viability of the shipping industry (Ahn et al, 2022).…”
Section: Budgeting Functions and The Determinants Of Their Executionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on smart ships has been actively pursued, and various methodologies and network architectures that can smoothly collect data from ships in operation have been proposed. This research has included areas such as big data collection systems [3], cyber security considerations [4], data management to reduce learning costs [5], framework structures for index systems [6], surveys of architectures and applications [7], and priority items for smart shipping [8]. Furthermore, various data on actual ships is being collected, Appl.…”
Section: Introductionmentioning
confidence: 99%
“…Studies consistently indicate that the implementation of digitalization has a positive impact on enterprise performance, including financial achievements [30], [31], [32], [33], [34], [35], [36] and a company's sustainable development goals [37], [38], [39]. However, these studies predominantly focus on the effects of digitalization in the operational aspects of the enterprise, with limited attention given to supporting (managerial) processes, particularly budgeting and budgetary control.…”
Section: Introductionmentioning
confidence: 99%